"Roots and Routes": Professional Educators’ Transformative Insights Into the Linguistic and Experiential Worlds of Generation 1.5 Language Minority Students (LEARNing Landscapes, 2015)
This article explores findings of a project that addressed the academic literacy development of children who are born and/or begin their formal schooling in Canada, but who are raised in homes where the societally dominant language is not the primary idiom. It focuses on collaborating educators’ professional learning through engagement in community-referenced action research that provided opportunities for eighth graders to explore themes related to their developing personal and socially situated identities. One key insight pertained to students’ access to information regarding their family histories and trajectories; a second, to linguistic dynamics internal to generation 1.5 linguistic minority youths’ households.
Keywords: teacher research; language; identity; students; literacy